2014
DOI: 10.3171/2014.1.focus13525
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraoperative computed tomography image-guided surgery in placing pedicle and pelvic screws for primary versus revision spine surgery

Abstract: Object Revision spine surgery, which is challenging due to disrupted anatomy, poor fluoroscopic imaging, and altered tactile feedback, may benefit from CT image-guided surgery (CT-IGS). This study evaluates accuracy of CT-IGS–navigated screws in primary versus revision spine surgery. Methods Pedicle and pelvic screws placed with the O-arm in 28 primary (313 screws) and 33 revision (429 screws) cases in which institutional postoperative CT scans were available were retrospectively reviewed for placement accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 13 publications
2
10
0
2
Order By: Relevance
“…Neuronavigation technologies have evolved significantly in spine surgery during the last decades and have provided significant advantages as an adjunct to minimally invasive surgical techniques (56). The reported accuracy in PS placement when fluoroscopic guidance is used ranges between 79.8% and 96.9% (26,28,30,(34)(35)(36)46,54,(57)(58)(59) while the intraoperative CT-based navigation technique is between 95.3% and 100% (60)(61)(62)(63), and the robotic guidance technique between 83.6% and 100% (46,49,(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronavigation technologies have evolved significantly in spine surgery during the last decades and have provided significant advantages as an adjunct to minimally invasive surgical techniques (56). The reported accuracy in PS placement when fluoroscopic guidance is used ranges between 79.8% and 96.9% (26,28,30,(34)(35)(36)46,54,(57)(58)(59) while the intraoperative CT-based navigation technique is between 95.3% and 100% (60)(61)(62)(63), and the robotic guidance technique between 83.6% and 100% (46,49,(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Examples of these techniques include the use of anatomic landmarks, 7 laminotomy for palpation of the pedicle, plain radiography, fluoroscopic imaging (standard or image guidance), 8,9 and CT image guidance. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Extensive literature has been published describing the technique, benefits, and drawbacks of each method, as well as comparisons between different approaches. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] With its increasing use has come a multitude of studies regarding the safety of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that 12.4% (24/193) iliac screw breaches could develop even with a 10-year experienced spinal surgeon, and especially occurred in the younger patients and post AIS surgery. We believe that this might be associated with revision surgery after AIS surgery in the relatively younger patients and could affect the high misplaced rates 6) .…”
Section: Discussionmentioning
confidence: 99%